Manfaat Sosial Ekonomi Energi Terbarukan:Kasus Negara-negara ASEAN - Syaifuddin Yana; Ardhana Yulisma; T.M. Zulfikar (Fakultas Teknik, 2022)
The development of renewable energy sources continues in the ASEAN region to meet the ASEAN energy mix target of 23% in 2025 and 31% in 2050. This is to meet the region's estimated 50% increase in energy demand. Renewable energy development projects in the ASEAN region have a beneficial effect on the ASEAN community's social life. This research is a review of the literature, examining journals on the socioeconomic benefits of NRE development through the lens of ASEAN member countries. Several conclusions can be drawn from the analysis's findings, including the following: (1) this renewable energy project can alleviate poverty by involving community members in utilizing natural resources to build power plants; (2) the creation of new jobs; (3) gross domestic product (GDP) is projected to increase by 2.5 percent in 2050; (4) the establishment of gender equality for women in the use of energy for regional development; and (5) an increase in education and scholastic achievement. The ASEAN region